2009
DOI: 10.1016/j.tips.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Siglecs as targets for therapy in immune-cell-mediated disease

Abstract: The sialic acid-binding immunoglobulin-like lectins (siglecs) comprise a family of receptors that are differentially expressed on leukocytes and other immune cells. The restricted expression of several siglecs to one or a few cell types makes them attractive targets for cell-directed therapies. The anti-CD33 (Siglec-3) antibody Gemtuzumab (Mylotarg™) is approved for treatment of acute myeloid leukemia (AML), and antibodies targeting CD22 (Siglec-2) are currently in clinical trials for treatment of B cell non-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
156
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 97 publications
4
156
0
Order By: Relevance
“…None of these mutations is currently considered a disease-initiating event and previous studies have suggested the absence of mutual exclusivity amongst mutations; clonal hierarchy could not be predicted when two or more of these mutations co-exist in the same patient. 1 The recent discovery of LNK mutations in JAK2V617F-negative MPN suggested an alternative mechanism of JAK-STAT (Janus kinase/signal transducers and activators of transcription) activation and clonal erythrocytosis. 2,3 However, subsequent studies showed that JAK2 and LNK mutations are not necessarily mutually exclusive and the pathogenetic contribution of LNK mutations, in the presence of JAK2V617F, remains unclear.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these mutations is currently considered a disease-initiating event and previous studies have suggested the absence of mutual exclusivity amongst mutations; clonal hierarchy could not be predicted when two or more of these mutations co-exist in the same patient. 1 The recent discovery of LNK mutations in JAK2V617F-negative MPN suggested an alternative mechanism of JAK-STAT (Janus kinase/signal transducers and activators of transcription) activation and clonal erythrocytosis. 2,3 However, subsequent studies showed that JAK2 and LNK mutations are not necessarily mutually exclusive and the pathogenetic contribution of LNK mutations, in the presence of JAK2V617F, remains unclear.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Therefore, CD33 appears as promising target for immunotherapy. 1 As surface-bound immune complexes from previously described anti-CD33 antibodies are rapidly uptaken by AML blasts within the first hours, previous anti-CD33 immunotargeting strategies were mainly based on toxic drugs, which were covalently bound to the anti-CD33 antibodies (for example, gemtuzumab ozogamicin, Mylotarg) and, thereby, co-delivered to the AML cells. 2 Unfortunately, the European approval of gemtuzumab failed and recently the drug was also withdrawn from the American market for reasons of side effects.…”
mentioning
confidence: 99%
“…Through a nomenclature agreement, Siglecs unique to mice are lettered rather than numbered (Crocker et al, 1998). Despite the discovery of numerous Siglecs, the biological functions of these proteins are largely unknown, although it has been reported that Siglec-8 specifically induces eosinophil apoptosis (O′Reilly and Paulson, 2009), while Siglec-9, which is expressed on the leukocyte surface, specifically induces neutrophil death (von Gunten et al, 2005). Investigations of Siglec biology have focused on the mouse as a model organism due to the difficulties and limitations associated with this type of research in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Using the STAR subtractive cloning technology (2), we identified sialic acid binding immunoglobulin-like lectin-15 (Siglec-15) as an mRNA transcript highly up-regulated in mature osteoclasts compared with their non-differentiated precursor cells (3). The Siglecs are a family of type I transmembrane proteins that are distinguished by N-terminal immunoglobulin-like domains that bind to sialylated glycoconjugates and are typically expressed in subsets of hematopoietic cell types (4). We examined the importance of Siglec-15 in tissue culture models of osteoclastogenesis and found that RNAi-mediated knockdown of Siglec-15 expression impaired RANKL-induced differentiation of primary human osteoclast precursors (HOPs) and the mouse RAW264.7 cell line (3).…”
mentioning
confidence: 99%